2015
DOI: 10.1016/j.jana.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding HIV-related Stigma Among Indonesian Nurses

Abstract: Evidence indicates widespread stigmatization of persons living with HIV (PLWH) in Indonesia. Such attitudes among health care workers could impede the country’s policies for effective diagnosis and medical treatment of PLWH. Nonetheless, research to guide interventions to reduce stigma in health care settings is lacking. Also, the contributions of workplace, religion, and HIV knowledge to nurses’ HIV-related stigma are poorly understood. Our cross-sectional study aimed to describe factors associated with nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 25 publications
5
70
0
8
Order By: Relevance
“…This condition reflects discrimination in HIV disease. Literature agree that stigmatisation is still a problem, and it is not only from the community, but also from the health care professional such as nurses and doctors [16], [17]. Stigma have been reported to cause burdens emotionally, physically and financially for people suffering HIV [18].…”
Section: Discussionmentioning
confidence: 99%
“…This condition reflects discrimination in HIV disease. Literature agree that stigmatisation is still a problem, and it is not only from the community, but also from the health care professional such as nurses and doctors [16], [17]. Stigma have been reported to cause burdens emotionally, physically and financially for people suffering HIV [18].…”
Section: Discussionmentioning
confidence: 99%
“…Stigma may result in people at risk for HIV delaying testing (Pottie et al, 2014) and lead to HCP providing differential care to PLWH (Mill et al, 2013). Stigma perpetuated by nurses may be related to a lack of knowledge and educational preparation about HIV clinical management and counseling, religious background, or workplace culture (Waluyo, Culbert, Levy, & Norr, 2015).…”
Section: Disclosuresmentioning
confidence: 99%
“…Stigma may result in people at risk for HIV delaying testing (Pottie et al, 2014) and lead to HCP providing differential care to PLWH (Mill et al, 2013). Stigma perpetuated by nurses may be related to a lack of knowledge and educational preparation about HIV clinical management and counseling, religious background, or workplace culture (Waluyo, Culbert, Levy, & Norr, 2015).HIV education for HCP is important to promote best practices. Education increases knowledge and promotes positive changes in attitudes, making it key to addressing HIV stigma in health care settings (Aggleton, Yankah, & Crewe, 2011).…”
mentioning
confidence: 99%
“…Despite earlier predictions which suggested that Islamic countries face a low prevalence of AIDS [13], HIV/AIDS is a public health disaster all over the world even in Islamic countries like Indonesia which have had rapidly expanding HIV epidemics in recent years [14]. According to Iran's Ministry of Health reports, HIV/AIDS continues to be debated and is a major threat to public health in Iran; therefore, research in this regard is important for the country [15].…”
Section: Introductionmentioning
confidence: 95%